Narrative Assets In Video Games As Linguistic’s Research - Khadifa Abdul Rozzaq Wijaya, Rahmaditya; Murti Wardhani, Evi; Faturrahman Bataiv, Misbah; Dzaky Kamaluddin, Ahnaf (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Video games are a type of digital entertainment that has shown substantial growth in both complexity and cultural significance since its creation in the mid-20th century. This study use a qualitative methodology, specifically the content analysis technique, to investigate and examine narrative elements in video games as a subject of linguistic inquiry. This approach aligns with Klaus Krippendorff's theory presented in Content Analysis: An Introduction to Its Methodology (2004). Krippendorff's theory posits that content analysis enables researchers to interpret the significance of different forms of texts and media portrayals, such as dialogue and narration in video games. This research reveals that narrative assets in video games can be analyzed through various linguistic approaches, including pragmatics, sociolinguistics, and Appraisal System, to better understand how language in digital narratives creates complex experiences for players